2018
DOI: 10.1111/ahe.12411
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomical studies on the glandular stomach of the rock pigeon (Columba livia targia) and the Egyptian laughing dove (Streptopelia senegalensis aegyptiaca)

Abstract: The rock pigeon (RP) and the laughing dove (LD) are common and widely distributed species in African countries, including Egypt. The present work was carried out to characterize the comparative features of the glandular stomach (proventriculus) in these two birds, which share diets and habitats. In both species, the proventriculus is an elongated spindle obliquely situated in the cranial two‐thirds of the body cavity. The length and weight of the proventriculus in the RP were about one and half times greater t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 12 publications
21
21
0
1
Order By: Relevance
“…Whereas, El Nahla, El Mahdy, and Basha (2011) in cattle egret reported that the stomach was composed of cranial proventriculus, caudal ventriculus, and small pyloric part. Between the proventriculus and the gizzard the isthmus was found, coinciding with Hanafy et al (2020) in Garganey, Madkour and Mohamed (2019) in the rock pigeon and the Egyptian laughing dove, Zaher, El‐Ghareeb, Hamdi, and AbuAmod (2012) in coturnix coturnix , Hassouna (2001) in goose, turkey, sparrow, kestrel, hoopoe, owl, and darter, while Bezuidenhout (1986) in ostrich, Ibrahim (1992) in jackdaw and heron, El Bakary (1993) in purple, El‐Ghazali (2008) in Ibis, El Nahla et al (2011) in cattle egret, Abumandour (2014) in Eurasian hobby reported its absence.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Whereas, El Nahla, El Mahdy, and Basha (2011) in cattle egret reported that the stomach was composed of cranial proventriculus, caudal ventriculus, and small pyloric part. Between the proventriculus and the gizzard the isthmus was found, coinciding with Hanafy et al (2020) in Garganey, Madkour and Mohamed (2019) in the rock pigeon and the Egyptian laughing dove, Zaher, El‐Ghareeb, Hamdi, and AbuAmod (2012) in coturnix coturnix , Hassouna (2001) in goose, turkey, sparrow, kestrel, hoopoe, owl, and darter, while Bezuidenhout (1986) in ostrich, Ibrahim (1992) in jackdaw and heron, El Bakary (1993) in purple, El‐Ghazali (2008) in Ibis, El Nahla et al (2011) in cattle egret, Abumandour (2014) in Eurasian hobby reported its absence.…”
Section: Discussionsupporting
confidence: 83%
“…The present investigation declared that the stomach of the Eurasian common moorhen consisted of proventriculus and gizzard. This coincides with Dursun (2002) in the domestic birds, Hanafy et al (2020) in Garganey, Ince, Pazvant, and Kahvecioglu (2010) in sea gull, and Madkour and Mohamed (2019) in the rock pigeon and the Egyptian laughing dove. Whereas, El Nahla, El Mahdy, and Basha (2011) in cattle egret reported that the stomach was composed of cranial proventriculus, caudal ventriculus, and small pyloric part.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Laughing dove (LD; Spilopelia senegalensis) is classified in the family Columbidaes and is found in South Africa (Madkour and Mohamed, 2019). Few previous studies have recorded the reproduction of birds in southern Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The laughing dove (Streptopelia senegalensis) is a small pigeon that is a resident breeder in Sub-Saharan Africa, the Middle East to the Indian Subcontinent as well as in Egypt (Madkour and Mohamed, 2019) This small long-tailed dove is found in dry scrub and semi-desert habitats where pairs can often be seen feeding on the ground (Bird Life International, 2015). Helminthes are major parasites of poultry animal.…”
Section: Introductionmentioning
confidence: 99%